PREDICTION OF THE PRIMARY SOURCES OF GIANT CLIPPIR DIAMONDS IN THE NORTH OF YAKUTIA BY THE METHOD OF MINERALOGICAL AND GEOCHEMICAL ANALOGY (METHOD 5E DIAGRAMS) - A. S. Ivanov; V. N. Zinchenko; I. V. Ashchepkov; S. A. Babushkina; O. B. Oleinikov; P. N. Shelkov (Геодинамика и тектонофизика, 2024)
The finds of giant CLIPPIR-type diamonds in the placers hosted by the Ebelyakh River basin in the north of Yakutia suggest that similar diamonds can be found in the kimberlites of the Anabar region and the nearest northern deposits located within the collisional Khapchan and Daldyn terranes. To predict the discovery of such diamonds, the authors use the 5E diagram method based on the principle of similarity of the compositions of five oxides of satellite minerals (Grt, Cpx, Chr and Ilm) of diamond (DSM) with the reference diagrams for the Karowe pipe (K-6, Botswana) with the composition of those for any other pipe. It was previously shown that the convergence of the DSM compositions of the Karowe and V. Grib (Arkhangelsk diamond province) pipes is 74 %, which might indicate possible presence of CLIPPIR diamonds in the predicted pipe. The application of this technique to two kimberlite pipes of the Anabar region demonstrated that the probability of detecting such diamonds in the Leningrad pipe (Lower Devonian, medium diamond content potential) is 74 %, and in the Malokuonamskaya pipe (Lower Triassic, medium diamond content) is 20 %. A comparison of diagrams 5E and additional PTС – fO2 diagrams of reconstructed sections of the lithospheric mantle showed their efficiency in predicting favorable conditions of CLIPPIR-type diamond crystallization. It is assumed that formation of such diamonds may occur within the proto-kimberlite magmatic chamber located near the boundary of the lithosphere and associated with the asthenospheric source. It should be surrounded by low-oxidized carbon-rich mantle eclogites and dunites with high pressure and temperature, as well as magnesium-rich ilmenite-chromite metasomatites. The use of the 5E diagram method, as the approach to predict giant CLIPPIR diamonds in poorly diamondiferous kimberlites, might attract investing for exploration to audit the industrial potential of a series of such kimberlites in the Anabar region. Its implementation would significantly increase the efficiency of geological exploration and assessment of the potential of poorly diamondiferous pipes that have been suspended as subeconomic.